Pengingkaran Kewajiban Negara dalam Pemenuhan Hak atas Kesehatan melalui Program BPJS di Tanjung Sari, Jambi Timur - Nurmalia Dewi; Amanda Kurnia Dwi Putri; Agum Shohefi; Fania Fitri Azkaria; Ulvia Rosayida; Nabilla Fatin; Fenita Paradiba (Pusat riset dan Inovasi Nasional, 2025)
This study aims to identify forms of violations of the right to health services in the implementation of BPJS Kesehatan, analyze the factors that cause them, and formulate preventive and limiting solutions. The research used a descriptive qualitative approach with in-depth interviews with six informants who were active BPJS Health participants in Tanjung Sari, East Jambi. The results showed that there was service discrimination in the form of different treatment between BPJS patients and general patients, patient rejection, administrative obstacles in emergency situations, and unavailability of drugs and medical facilities. Contributing factors include unequal distribution of health facilities, limited human resources, and a weak monitoring system. The experiences of BPJS participants confirm the gap between the program's objectives and the reality on the ground, reflecting a denial of the state's obligation to guarantee citizens' health rights. Comprehensive efforts are needed, including public education, administrative simplification, equitable distribution of health facilities, enforcement of strict sanctions, and active community involvement to realize quality and equitable health services.